Differences in compassion satisfaction and compassion fatigue among oncology nurses in Oman: A multi-center cross-sectional study - Devakirubai Jacob; Joshua K. Muliira; Eilean R. Lazarus; Omar Al Zaabi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Oncology nurses are constantly exposed to occupational exposure to the suffering of others, which can lead to vicarious traumatization, low professional quality of life (ProQOL), and inability to provide quality nursing care. The purpose of the study is to explore the ProQOL of oncology nurses working in Oman and the characteristics that lead to differences in compassion satisfaction (CS) and compassion fatigue (CF). MATERIALS AND METHODS: A cross-sectional design was conducted between March and December 2020 using the ProQOL scale to collect data from 242 oncology nurses in Oman using a convenience sampling technique. The rates of CS and CF [(secondary traumatic stress (STS) and burnout (BO)] were summarized using descriptive statistics. The characteristics leading to differences in CS and CF were assessed using the independent-sample t-test. RESULTS: Only 35% reported high levels of CS. Most nurses reported moderate STS (60%) and BO (65%). Nurses aged ≥36 years, ≥10 years of professional experience, ≥6 years of oncology experience, married, and desiring to work with cancer patients reported higher levels of CS. CONCLUSION: Omani oncology nurses have low levels of CS. The nurses' desire to work with cancer patients, professional experience, and the age of cancer patients regularly affected the experience of CF. The identified characteristics can be exploited to mitigate deterioration in oncology nurses' ProQOL using targeted interventions for high-risk individuals. Beneficial interventions may focus on continuing education, stress management, coping, work environment, teamwork, and communication of oncology nurses and other members of the healthcare team.